Perspectives on the value of BECCS: The Cost of Bio Energy Carbon Capture and Storage in the Pulp and Paper Supply Chain - Klement, Jonathan (My University, 2019)
To prevent a devastating global temperature increase the concentration of greenhouse gases (GHG) should not increase. However, the concentration of GHG in the atmosphere is already at a level, that most pathways to global temperature targets require negative-emission tech-nologies (NET), which remove GHG from the atmosphere. One of these NETs is Bio energy carbon capture and storage (BECCS). In Sweden, 30% of the current fossil GHG emissions could be offset using this technology. Despite the need, currently, NET applications are not recognized as carbon mitigation for private developers. Thus, there is no value to a plant op-erator in applying BECCS. This thesis argues therefore for a value of reduced carbon emission through BECCS in pulp making. It evaluates the cost increase and emission reduction of products down the supply chain until the end-user. Packaged drinks, a corrugated board box and a book were identified as representative paper products for the analysis. The changes of costs and carbon footprint through BECCS are then related to the price and carbon footprint of consumer products. It was found that the cost increase, resulting from implementation of BECCS in pulp and paper in-dustry, would remain within the range of 0.1%- 0.2% for the investigated low value products. As the products’ respective carbon footprint can be reduced substantially by attributing the captured carbon to the product (i.e. 3% -91%), the intangible value in low-carbon products increases, too. The industry of investigation in this thesis is the Swedish pulp and paper industry, which con-stitutes Sweden’s largest energy consuming and GHG emitting industry. The industry’s energy supply is dominated by bioenergy and the GHG emissions consequently are predominantly of biogenic origin, making it a relevant industry for BECCS application. The work concludes that the additional perspectives on the value of emission control helps to remove communication barriers that may have prevented the implementation of BECCS. With this supply chain perspective on BECCS, pulp producers (possibly in collaboration with supply chain partners) could have a reason to unlock investments and start mitigating climate change through pulp production, even without political incentives.
Keywords: BECCS costs, BECCS barrier, negative emission technology, incentive, accounting, pulp and paper industry, carbon neutral, supply chain, value chain, carbon footprint, Sweden